Explicit and approximate solutions of a class of evolution problems in hilbert space. (December 2019) - Gavrilyuk, Ivan P.; Makarov, Vladimir L.
Abstract : Explicit closed-form solutions for a class of first order evolution problems in a Hilbert space are presented. On the basis of these explicit representations we construct approximations adapted to the regularity of the initial data.